PENGARUH CURRENT RATIO (CR) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT. SURYA CITRA MEDIA (SCM) Tbk. PERIODE 2012-2021 - Anisa Rahmadhani; Nurismalatri Nurismalatri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of Current Ratio (CR) and Earning Per Share (EPS) on stock prices at PT. Surya Citra Media (SCM), Tbk for the period 2012–2021. The research method used in this research is associative quantitative. The population in this research is the Financial Report of PT. Surya Citra Media (SCM) Tbk. The sample in this research is the Balance Sheet and Profit and Loss Financial Report of PT. Surya Citra Media (SCM) Tbk. 2012-2021. The data analysis methods used are descriptive statistical analysis, classical assumption test, multiple linear regression test, t test, F test and determination test with the help of the Eviews12 software program. Based on the research results of the t test analysis, it was found that the Current Ratio (CR) variable had a value of tcount (-1.046512) < ttable (1.894579) and a significance value of (0.3301) > (0.05), so Ho was rejected and Ha was accepted, meaning Current Ratio (CR) does not have a positive influence on stock prices. Meanwhile, for the Earning Per Share (EPS) variable, the value obtained is tcount (5.935955) > ttable (1.894579) and the significance value is (0.0006) < (0.05), so Ho is accepted and Ha is rejected, meaning that partially Earning Per Share (EPS) has a positive influence and significant to stock prices. In the F test, it shows that the Fcount value is (18.46942) > (4.74), and the significance value is (0.001614) < (0.05), so it can be said that the Current Ratio (CR) and Earning Per Share (EPS) are together or simultaneously has a significant influence on stock prices. As well as having a coefficient of determination with a value of 0.973261, this shows that 79.5% of the Current Ratio (CR) and Earning Per Share (EPS) together have an effect on the stock prices.